Analysis of Determinants the Foreign Exchange Earnings of Tourism Sector in Indonesia - Dyike Adella Ramdhani; Dedi Supriadi; Barokatuminalloh Barokatuminalloh (Faculty of Economics and Business, Jenderal Soedirman University, 2017)
This research aims to analyze determinants of the number of foreign tourist, average foreign tourist expenditure, average length of stay foreign tourist, and dollar exchange rate against rupiah on foreign exchange earnings of tourism sector in Indonesia 2009 – 2013 periods. The data is secondary from Indonesia Statistical Agency, Bank of Indonesia, Ministry of Tourism and Creative Economy, articles, journal, and result of previous researches. This research uses panel data regression analysis. The result shows that the number of foreign tourist, average foreign tourist expenditure, average length of stay foreign tourist and dollar exchange rate against rupiah are giving positive effect on foreign exchange earnings of tourism sector in Indonesia 2009 – 2013 periods. Average length of stay foreign tourist is a variable that mostly affecting on open foreign exchange earnings in Indonesia 2009 – 2013 periods. Based on the result, the government is targeting foreign tourist arrivals to Indonesia for foreign tourists bringing foreign currency so that the rupiah demand will rise and increase tourism foreign exchange. Government, investors and communities leveraging existing infrastructure so that the average length of stay of foreign tourists continues to increase so Enhancing tourism foreign exchange. Stability of rupiah should always be maintained.